Determinants of Environmental Quality in Africa - Onyeneke Robert Ugochukwu; Chidiebere-Mark Nneka Maris; Ejike Roseline Daberechi; Chikezie Comfort; Uhuegbulem Ifeyinwa Josephine (Ekológia (Bratislava))
Africa has diverse ecosystems and abundant natural resources crucial for its growth and development. Unsustainable use of natural resources can increase the ecological footprint and lead to environmental deterioration on the continent. Several factors influence ecological footprint – a proxy for environmental degradation. However, literature on the determinants of ecological footprint in Africa is mixed and without any evidence on the effect on different quantiles/groups. Therefore, this paper explored the impact of agricultural production, renewable energy, rule of law, natural resource dependence and foreign investments on ecological footprint in Africa controlling for economic growth. We used data from 44 countries in Africa spanning a period of 21 years (2000–2020) and applied fixed effects and method of moment quantile regression models for analysis. Our findings show that GDP per capita, livestock production and foreign direct investments had significant positive association with ecological footprint for most of the quantiles. In contrast, renewable energy consumption, crop production index, rule of law, urbanisation and natural resource rents all reduced ecological footprint in Africa for most of the quantiles. Continuous law enforcement in Africa combined with investment in renewable energy, sustainable crop production practices and sustainable management of natural resources would reduce the continent’s ecological footprint and environmental degradation.